Activation of the P–H bond by a frustrated Lewis pair and its application in catalytic Z-selective hydrophosphonylation of terminal ynones. Issue 79 (26th July 2017) - Liu, Yizhen; Fan, Xiaoting; Li, Zhen Hua; Wang, Huadong
Abstract : Z -Selective hydrophosphonylation of terminal ynones was achieved by employing a frustrated Lewis pair catalyst. Abstract : The frustrated Lewis pair (FLP) comprised of B(C6 F5 )3 and 1, 2, 2, 6, 6-pentamethylpiperidine (PMP) can efficiently catalyze Z -selective hydrophosphonylation of terminal ynones with a Z / E selectivity of up to 20 : 1. Mechanistic studies suggest that the trans arrangement of the phosphite nucleophilic attack and hydrogen bond formation on the alkyne moiety is responsible for the observed Z -selectivity.